Experimental analysis on Feed force reduction performance by nano fluid of nano- alumina particles enriched waste coconut oil in wet machining of SAE 1045 steel shaft. (2022) - Anbuchezhiyan, G.; Saravanan, R.; Pugazhenthi, R.; Ananda Kumar, Eriki; Arunkumar, K.
Highlights: Waste coconut oil is utilized for preparing a novel Nano fluid. Feed force at clean and green machining environment. Minimum Feed force at 40 m/min cutting velocity 0.05 tool feed 1.2 mm depth of cut. Waste coconut oil based wet machining method reduces the Feed forces averagely by 35.83% Abstract: Waste utilization is act of clean technology. The multiple times used cooking oils are called as waste cooking oil. This investigation focuses specific type of such vegetable oil (coconut oil) for synthesizing the nanofluid for metal machining purposes Used coconut oils are considered as waste and disposed on open channel and that is against to eco-friendliest. The use of such liquid waste for machining coolant is investigated in this piece of research. Liquid Waste used for creating nanofluid for metal cutting is novel approach. If it is feasible the coolant cost will be significantly reduced and waste such oil disposal will also be reduced. This piece of research work aims to investigate the effect of Nano- alumina based Nanofluid in machining of steel work in the lathe machine. The novelty in this investigation is the used coconut oil is reused as base fluid for preparing the nanofluid. Feed force response is used for optimizing the parameters of the metal removal process. For investigating the effects, the cutting speed varied as 40 to 190 m/min, feed rate of the tool varied as 0.05 to 0.20 mm/rev and the CVD coated tool with 4 different nose radiuses used such as 0.3 mm, 0.6 mm 0.9 mm, and 1.2 mm, L16 orthogonal array involved to form the minimum experimental combinations. The results compared with existing practice of dry machining. The test revels that the feasibility of use of liquid waste of used coconut oil for coolant as in the proposed Nanofluid form. The new fluid based cutting out performed and its process parameters influences were studied, optimized and mathematical model developed for prediction of feed force. The Nanofluid reduced the cutting force averagely 35.83%